Different way to calculate a different mean

Calculus Level 5

You may have heard of the arithmetic-geometric mean agm ( x , y ) \text{agm}(x,y) . Let us define the arithmetic-harmonic mean ahm ( x , y ) \text{ahm}(x,y) as such:

Let x = a 0 x = a_{0} and y = h 0 y = h_{0} , and define a n + 1 = a n + h n 2 a_{n+1} = \frac{a_{n}+h_{n}}{2} and h n + 1 = 2 1 a n + 1 h n h_{n+1} = \frac{2}{\frac{1}{a_{n}}+\frac{1}{h_{n}}} . Then ahm ( x , y ) = lim n a n = lim n h n \displaystyle \text{ahm}(x,y) = \lim_{n \rightarrow \infty} a_{n} = \lim_{n \rightarrow \infty} h_{n} .

Evaluate

ahm ( 2 1 , ahm ( 2 4 , ahm ( 2 9 , ahm ( 2 16 , ) ) ) ) \text{ahm}(2^{1}, \text{ahm}(2^{4}, \text{ahm}(2^{9}, \text{ahm}(2^{16}, \ldots))))


The answer is 64.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Jake Lai
May 3, 2015

The arithmetic-harmonic mean converges to the geometric mean. This can be seen by the invariance of the GM after each iteration:

a n h n = a n + h n a n + h n a n h n = a n + h n 1 a n + 1 h n = a n + h n 2 2 1 a n + 1 h n = a n + 1 h n + 1 \sqrt{a_{n}h_{n}} = \sqrt{\frac{a_{n}+h_{n}}{\frac{a_{n}+h_{n}}{a_{n}h_{n}}}} = \sqrt{\frac{a_{n}+h_{n}}{\frac{1}{a_{n}}+\frac{1}{h_{n}}}} = \sqrt{\frac{a_{n}+h_{n}}{2} \frac{2}{\frac{1}{a_{n}}+\frac{1}{h_{n}}}} = \sqrt{a_{n+1}h_{n+1}}

So what we're dealing with is the nested radical

2 1 2 4 2 9 = 2 1 2 / 2 1 2 2 2 / 2 2 2 3 2 / 2 3 \sqrt{2^{1}\sqrt{2^{4}\sqrt{2^{9}\sqrt{\ldots}}}} = 2^{1^{2}/2^{1}} \cdot 2^{2^{2}/2^{2}} \cdot 2^{3^{2}/2^{3}} \cdot \ldots

Taking log base 2 2 gives us the infinite sum

n = 1 n 2 2 n \sum_{n=1}^{\infty} \frac{n^{2}}{2^{n}}

It is well-known that n = 1 x n = x 1 x \displaystyle \sum_{n=1}^{\infty} x^{n} = \frac{x}{1-x} for all x < 1 |x| < 1 . Differentiating both sides and multiplying by x x gives us the identity n = 1 n x n = x ( 1 x ) 2 \displaystyle \sum_{n=1}^{\infty} nx^{n} = \frac{x}{(1-x)^{2}} . Again differentiating and multiplying x x gives us n = 1 n 2 x n = x ( 1 + x ) ( 1 x ) 3 \displaystyle \sum_{n=1}^{\infty} n^{2}x^{n} = \frac{x(1+x)}{(1-x)^{3}} .

Since x = 1 2 x = \frac{1}{2} satisfies that x < 1 |x| < 1 , we can use the above identity to evaluate our infinite series:

n = 1 n 2 2 n = 1 2 ( 1 + 1 2 ) ( 1 1 2 ) 3 = 6 \sum_{n=1}^{\infty} \frac{n^{2}}{2^{n}} = \frac{\frac{1}{2}(1+\frac{1}{2})}{(1-\frac{1}{2})^{3}} = 6

Hence, the nested radical turns out to be 2 6 = 64 2^{6} = \boxed{64} . Hurrah!

Did the same! Thanks for the problem! You are great!

Kartik Sharma - 6 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...